Students’ Perceptions on Head Teacher Leadership Roles for Student Engagement at Secondary Schools in Bangladesh (Teacher’s World: Journal of Education and Research, 2024)
The active involvement of students in the educational process is of utmost importance in guaranteeing the provision of high-quality education. Headteachers have the capacity to assume a substantial role in fostering student engagement in various school activities. The primary objective of this study was to investigate the perspectives of students regarding the role of the head teacher in promoting student engagement within secondary schools in Bangladesh. The research was conducted utilizing a qualitative approach. In order to accommodate the convenience of eight schools representing eight divisions in Bangladesh, a total of eight Focus Group Discussions (FGDs) were conducted. The findings of this study indicate that the leadership exhibited by head teachers has a discernible influence on the level of student engagement. The head teachers’ leadership positions encompassed several important responsibilities, such as overseeing and assessing the academic activities and progress of students, offering guidance and motivation, fostering active participation in teaching and learning, as well as involving students in extracurricular pursuits and decision-making processes within the school context. This study also unveiled specific detrimental characteristics exhibited by head teachers that served as demotivating factors for student engagement in school activities. In order to enhance the quality of education, it has been recommended that secondary level head teachers in Bangladesh should augment the range of activities aimed at fostering student engagement within the school setting.Teacher’s World: Journal of Education and Research, 49 (1), 137-154